Handbook of modern and contemporary Japanese women writers - Copeland, Rebecca L., 1956- (Japan Documents handbooks., 2023)
The Handbook of Modern and Contemporary Japanese Women Writers offers a comprehensive overview of women writers in Japan, from the late 19th century to the early 21st. Featuring 24 newly written contributions from scholars in the field-representing expertise from North America, Europe, Japan, and Australia-the Handbook introduces and analyzes works by modern and contemporary women writers that coalesce loosely around common themes, tropes, and genres. Putting writers from different generations in conversation with one another reveals the diverse ways they have responded to similar subjects. Whereas women writers may have shared concerns-the pressure to conform to gendered expectation, the tension between family responsibility and individual interests, the quest for self-affirmation-each writer invents her own approach. As readers will see, we have writers who turn to memoir and autobiography, while others prefer to imagine fabulous fictional worlds. Some engage with the literary classics-whether Japanese, Chinese, or European-and invest their works with rich intertextual allusions. Other writers grapple with colonialism, militarism, nationalism, and industrialization. This Handbook builds a foundation which invites readers to launch their own investigations into women's writing in Japan.